The practice of deliberative democracy in the Temerloh Parliamentary Consultative Council (TPCC), Malaysia - Mohd Sani, Mohd Azizuddin; Omar, Rusdi; Kasim, Azahar; Abdullah, Mohamad Ainuddin Iskandar Lee; Mukhtaruddin, Mas Juliana; Abdullah, Ahmad Amir (Medwell Journal, 2013)
This study attempts to analyse a shift in decision-making approach for Malaysia’s local government. Since the 12th general election in 2008, people participation in decision-making process has become very important in order for the government to produce a people friendly public policy. Therefore, this study takes the opportunity to study a model of deliberative democracy which has been introduced through the Temerloh Parliamentary Consultative Council (TPCC) by Deputy Minister in the Ministry of Higher Education, Saifuddin Abdullah. Model that has been introduced by Saifuddin is one of its kinds which has never been practiced before in Malaysia as an agenda for effective governance. The intention of this study is to analyse the effectiveness of the TPCC Model whether it can be the best model for public deliberation in Malaysia.